The Meaning of Environmental Cleanliness (A Phenomenological Study of Waste Managementin Serang City) - Marthalena, Marthalena; Berthanila, Rethorika; Santi, Endang Tri (Future Science, 2025)
This study aims to understand the meaning of environmental cleanliness from the perspective of the people of Serang City through a phenomenological approach, focusing on practices and perceptions related to waste management. Serang City, as the capital of Banten Province, faces serious challenges in waste management due to population growth and consumption patterns. This study employs a qualitative method with a phenomenological approach, where data is collected through in-depth interviews with residents, sanitation workers, and waste managers. The results indicate that the meaning of environmental cleanliness is not only understood physically as being free from waste but is also closely tied to social, cultural, and religious values. The community perceives cleanliness as a form of collective responsibility that reflects awareness of environmental sustainability and quality of life. However, there is still a gap between understanding and actual practice in the field, particularly regarding the lack of facilities and insufficient environmental education. This study recommends the need for a participatory and educational approach to waste management so that the meaning of environmental cleanliness can be realised more comprehensively and sustainably in Serang City.